Hubungan Tingkat Pendidikan Ibu dengan Kelengkapan Imunisasi Dasar Di Wilayah Kerja Puskesmas Sungai Tabuk 1 Desa Pemakuan Tahun 2023 - Nur Syifa Mardhatillah; Suryati Suryati; Solikin Solikin (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Immunization is the process of administering vaccines aimed at providing protection or immunity against specific diseases. Immunization stimulates the body's immune system to recognize and fight disease infections more effectively, reducing the risk of individuals who have been vaccinated contracting the disease. Understanding the administration of immunization is crucial, especially in the current context where infections and diseases are highly dangerous and easily transmissible, such as tuberculosis, diphtheria, pertussis, tetanus, polio, hepatitis, and others. The purpose of this study is to determine the relationship between the mother's educational level and the completeness of basic immunization in the working area of ​​Sungai Tabuk 1 Community Health Center, Pemakuan Village, in the year 2023. The research design used is cross-sectional and was conducted in October 2023. The population consists of mothers with children aged ≥11, with a sample size of 112 respondents. Data were collected through the distribution of questionnaires and Maternal and Child Health Books (Buku KIA). The majority of mothers had a low level of education, amounting to 60 people with a percentage of 53.6%. Most respondents had complete basic immunization, totaling 77 respondents with a percentage of 68.8%. The Chi-Square Test analysis results show p = 0.000 < α (0.05), thus it is concluded that H0 is rejected, and Ha is accepted, indicating a relationship between the mother's educational level and the completeness of basic immunization in the working area of ​​Sungai Tabuk 1 Community Health Center, Pemakuan Village..